2018
DOI: 10.4028/www.scientific.net/jbbbe.37.107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glutaraldehyde on Hydroxyapatite-Gelatin Composite with Addition of Alendronate for Bone Filler Application

Abstract: Based on data from Indonesian Health Ministry in 2009, osteoporosis case reached 19,7 % of the populations in Indonesia, especially women in menopause period. The treatment was performed by consuming bisphosphonate drugs per oral which was not effective since the absorption intake of the drug was only less than 55% of the intake dosage. Because of that, the bone filler which also has a function as drug delivery system was developed. The hydroxyapatite-gelatin bone filler with the addition of alendronate was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The peak at wavenumber of 3467.5 cm −1 resembled the stretching vibration of hydroxyl group from the material used in this study, HA, GEL, HPMC, and streptomycin. The absorbance at wavenumber of 2929.47 cm −1 was the stretching vibration of C-CH 3 which was the specific functional group from HPMC [7]. The peak at 1648.49 cm −1 showed the bonding between the carbonyl functional group originated from gelatin and the amine group from the streptomycin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peak at wavenumber of 3467.5 cm −1 resembled the stretching vibration of hydroxyl group from the material used in this study, HA, GEL, HPMC, and streptomycin. The absorbance at wavenumber of 2929.47 cm −1 was the stretching vibration of C-CH 3 which was the specific functional group from HPMC [7]. The peak at 1648.49 cm −1 showed the bonding between the carbonyl functional group originated from gelatin and the amine group from the streptomycin.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxyapatite is one of the materials that could be used as bone graft [7]. This material has biocompatible and bioactive properties which is beneficial for restoring the bone defect due to the bone tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It showed that the specific functional group of every compound was in there, such as amide I stretching, C = O, C-O-C complex from chitosan, hyaluronic acid, and collagen at wavenumber of 1643.53, 1406.64, and 1082.67 cm -1 , respectively. The absorption peak at wavenumber of 3434.41 cm -1 was the hydroxyl functional group from every material and also the result of crosslinking [14,17,18]. There was a slight shift of absorption peak of amide I functional group which indicated the result of crosslinking process.…”
Section: Synthesis Of Collagen-hyaluronic Acid-peo-based Electrospun mentioning
confidence: 89%
“…A broadening peak around 300-3500 cm -1 is due to the interaction between the constituent elements of the composite, such as hydrogen bonding between chitosan-hydroxyapatite. The -OH and NH2 groups of chitosan bind with the -OH group of hydroxyapatite 24 . Figure-6a showed the XRD pattern for the composite, and showed that the composite consisted of mostly amorphous materials.…”
Section: Resultsmentioning
confidence: 99%